2012
DOI: 10.1364/josab.29.002524
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion relations of the modes for open nonhomogeneous waveguides terminated by perfectly matched layers

Abstract: The perfectly matched layer (PML) is a widely used tool to truncate the infinite domain in modal analysis for optical waveguides. Since the PML mimics the unbounded domain, propagation modes and leaky modes of the original unbounded waveguide can be derived. However, the presence of PML will introduce a series of new modes, which depend on the parameters of PML, and they are named as Berenger modes. For twodimensional step-index waveguides, the eigenmode problem is usually transformed into an algebraic equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In addition, Kim et al also defined and explained the regimes of these modes based on their physical meanings [15][16][17][18]. To solve the eigenvalue problems more efficiently, asymptotic formulas have been derived before using the numerical solvers for planar and circular multilayered structures [19][20][21][22][23]. The waveguides open to air or closed with perfect matching layer (PML) were considered, and Lambert W function [24,25] has been leveraged frequently to simplify the asymptotic expressions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kim et al also defined and explained the regimes of these modes based on their physical meanings [15][16][17][18]. To solve the eigenvalue problems more efficiently, asymptotic formulas have been derived before using the numerical solvers for planar and circular multilayered structures [19][20][21][22][23]. The waveguides open to air or closed with perfect matching layer (PML) were considered, and Lambert W function [24,25] has been leveraged frequently to simplify the asymptotic expressions.…”
Section: Introductionmentioning
confidence: 99%
“…Rogier et al [24] found the propagation constants of leaky modes of planar and circular dielectric waveguides terminated by a PML. In another work [25], we derived a dispersion relation for a nonhomogeneous waveguide with two PMLs for the TE case. However, for the TM case, the relation of the modes was not given in [25] because of the mathematical complexity.…”
Section: Introductionmentioning
confidence: 99%
“…In another work [25], we derived a dispersion relation for a nonhomogeneous waveguide with two PMLs for the TE case. However, for the TM case, the relation of the modes was not given in [25] because of the mathematical complexity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation